HUBUNGAN PENGETAHUAN AKSEPTOR KB TENTANG IUD DENGAN KEIKUTSERTAAN MENGGUNAKAN IUD DI PMB BDN. NI WAYAN SUSIANTI, S.S.T.KEB - Pasguniari, Ni Kadek Mianti; Mastiningsih, Putu; Yunita Udayani, Ni Putu Mirah; Kusuma Putra, Putu Wira (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2024)
Contraception is a method or tool used with the aim of preventing pregnancy. The decrease in the number of IUD family planning participants over the years can be caused by the participants' lack of knowledge about the advantages of IUD contraception. Knowledge of contraceptive devices is a consideration in determining the contraceptive method used. The quality of family planning services is seen in terms of the availability of health service personnel tools, the high cost of IUD services, and the existence of barriers from husband support in the use of IUD contraceptive devices. The purpose of this study is to determine the Relationship of Family Planning Acceptors' Knowledge About IUD With Participation in Using IUD at PMB Bdn. Ni Wayan Susianti, S.S.T.Keb. This study uses a correlational analytic design with a cross-sectional approach. The sample selection in this study used purposive sampling technique. The sample for this study is 40 acceptors. Data were analyzed using Chi-square test analysis. The results of the analysis using the Chi-square test showed that from 40 respondents, a p-value of 0.001 was obtained. This result indicates that H0 is rejected and Ha is accepted, which means there is a significant relationship between the knowledge of family planning acceptors about IUD and participation in using IUD at PMB Bdn. Ni Wayan Susianti, S.S.T.Keb. Based on the results of this study, it is hoped that family planning acceptors will increase their knowledge about IUD with participation in using IUD.